Species-specific enamel differences in hardness and abrasion resistance between the permanent incisors of cattle (Bos primigenius taurus) and the ever-growing incisors of nutria (Myocastor coypus) - Valentin L. Fischer; Daniela E. Winkler; Robert Głogowski; Thomas Attin; Jean-Michel Hatt; Marcus Clauss; Florian Wegehaupt (PLoS ONE, 2022)
Hypselodont (ever-growing) teeth of lagomorphs or rodents have higher wear rates (of a magnitude of mm/week), with compensating growth rates, compared to the non-ever-growing teeth of ungulates (with a magnitude of mm/year). Whether this is due to a fundamental difference in enamel hardness has not been investigated so far. We prepared enamel samples (n = 120 per species) from incisors of cattle (Bos primigenius taurus) and nutria (Myocastor coypus, hypselodont incisors) taken at slaughterhouses, and submitted them to indentation hardness testing. Subsequently, samples were split into 4 groups per species (n = 24 per species and group) that were assessed for abrasion susceptibility by a standardized brush test with a control (no added abrasives) and three treatment groups (using fine silt at 4 ±1 μm particle size, volcanic ash at 96 ±9 μm, or fine sand at 166 ±15 μm as abrasives), in which enamel abrasion was quantified as height loss by before-and-after profilometry. The difference in enamel hardness between the species was highly significant, with nutria enamel achieving 78% of the hardness of cattle enamel. In the control and the fine sand group, no enamel height loss was evident, which was attributed to the in vitro system in the latter group, where the sand particles were brushed out of the test slurry by the brushes’ bristles. For fine silt and volcanic ash, nutria enamel significantly lost 3.65 and 3.52 times more height than cattle. These results suggest a relationship between enamel hardness and susceptibility to abrasion. However, neither the pattern within the species nor across the species indicated a monotonous relationship between hardness and height loss; rather, the difference was due to qualitative step related to species. Hence, additional factors not measured in this study must be responsible for the differences in the enamel’s susceptibility to abrasion. While the in vitro brush system cannot be used to rank abrasive test substances in terms of their abrasiveness, it can differentiate abrasion susceptibility in dental tissue of different animal species. The results caution against considering enamel wear as a similar process across mammals.